EXPERIENCE-BASED KNOWLEDGE IN ISLAMIC PERSPECTIVE - yuli indah sari; Widiyanto bin Mislan Cokrohadisumarto; Olivia Fachrunnisa; Abdul Ghafar Ismail (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
The development of technology has created problems regarding challenges and opportunities to utilize the knowledge that humans get from experience to guard these developments. Experience-based knowledge has been seen as a special advantage for individuals and Islam has unique in explaining this aspect. This paper aims to develop an experience-based knowledge model from an Islamic perspective and be developed based on a literature review approach, as well as integrated with Islamic values ​​contained in the Quran and hadith. Human knowledge on God's earth can be obtained through; personal experiences, other people, expert experiences, and experiences that are narrated in the Quran and Hadith. These experiences help individuals improve their abilities (in receiving mandates) and spread knowledge to others to achieve Allah's blessings, renewal of knowledge, and help achieve organizational goals.